Tort Law - Elliott, Catherine, 1966-; Quinn, Frances, 1963- (Harlow : Longman, 2011)
As well as setting out the law itself, the authors examine the principles behind tort law, and discuss some of the issues and debates arising from it.
Previous ed.: 2009.
Includes bibliographical references and index.
Keywords: Torts -- England; Torts -- Wales; Law